ChemInform Abstract: Biological Importance of Structurally Diversified Chromenes. Issue 48 (10th November 2016) - Costa, Marta; Dias, Tatiana A.; Brito, Alexandra; Proenca, Fernanda
Abstract: Review: 166 refs.